Pengaruh Tingkat Pendidikan dan Pengalaman Kerja Terhadap Prestasi Kerja dengan Motivasi Kerja sebagai Variabel Intervening (Studi Kasus Karyawan bagian Produksi PT Tarumartani 1918) - Purbojati, Ziko; Kirana, Kusuma Chandra; Subiyanto, Didik (Ekonomis: Journal of Economics and Business, 2024)
This study aims to examine and analyze the effect of educational level and work experience on work performance with work motivation as an intervening variable. The population in this study were production employees at PT Tarumartani. The technique used in sampling in this study was simple random sampling, and a total sample of 65 employees of the Production division of PT Tarumartani was obtained as respondents. Data collection was carried out using the questionnaire method, then the data obtained was processed using Statistical Product and Service Solutions (SPSS). The results of this study indicate that the level of education has a significant effect on work performance, work experience does not have a significant effect on work performance, education level does not has a significant effect on work motivation, work experience has a significant effect on work motivation, work motivation has an effect on work performance.